Effects of moisture content on strength and compression properties of foundation soils of cultural relics in areas flooded by the Yellow River - Ma, Shaochun; Yao, Yudi; Bao, Peng; Guo, Chengchao (Frontiers in Materials, 2023)
This study investigated the effects of soil moisture content on the strength and deformation properties of the foundation soils of cultural relics. Our goal is to inform the formulation and implementation of the repair scheme for cultural relics above the foundation soils and help protect cultural relics. Soil samples with five different moisture contents were prepared and used in unconfined compression, triaxial, and consolidation tests. Several mechanical parameters were determined under different soil moisture contents: failure morphology, compressive strength, compressive modulus, and compressibility coefficient. Based on the test results, the soil cohesion and angle of internal friction were obtained using Mohr’s circle. Regions where the mechanical parameters were particularly sensitive to moisture content were located during the consolidation test. These were also the regions where the soil’s compressive modulus declined rapidly, which was detrimental to the overall stability and safety of overlying structures. The internal structure and particle size distribution of the foundation soils supporting cultural relics were determined by scanning electron microscopy. Constitutive parameters of soils were determined by the triaxial test and consolidation test. It was also found that when the soil moisture content exceeded the optimal level, the foundation soils were very likely to pose a risk to the safety of the overlying cultural relics. The moisture content of foundation soils supporting cultural relics deserves special attention in engineering practice.